The production of everyday life in eco-conscious households : compromise, conflict, complicity - Munro, Kirstin Marie Elizabeth, 1983- (Bristol University Press, 2023)
Drawing on qualitative fieldwork, this book sheds much-needed light on how sustainability-oriented households balance priorities and get things done in day-to-day life, offering crucial insights about eco-conscious living at an individual level.